2019
DOI: 10.1016/j.gca.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the discrepancy between the dehydration rates in mantle olivine and pyroxene during xenolith emplacement

Abstract: Hydrogen concentration profiles through olivine and pyroxene in peridotite xenoliths carried in rift basalts from northern Tanzania (Lashaine, Eledoi, and Kisite localities) show bell-shaped distributions, indicating that diffusive hydrogen loss has occurred in all minerals. Homogeneous major element concentrations and equilibration of hydrogen between the cores of olivine and coexisting pyroxene suggest that hydrogen loss resulted from diffusive degassing during host magma emplacement. For these samples, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 81 publications
3
12
0
Order By: Relevance
“…This is particularly relevant for our lower model temperatures, where the 100% re-equilibration timescales require melt flow for a few weeks to over a year for the different mineral phases ( Figure 5). Dis-equilibrium water contents between NAM phases could thus reflect differences in activation energy between Arrhenius relationships at a given temperature (Xu et al 2019) and H + diffusion may be useful for deciphering the timescales of this process.…”
Section: Melt-rock Interactionsmentioning
confidence: 99%
“…This is particularly relevant for our lower model temperatures, where the 100% re-equilibration timescales require melt flow for a few weeks to over a year for the different mineral phases ( Figure 5). Dis-equilibrium water contents between NAM phases could thus reflect differences in activation energy between Arrhenius relationships at a given temperature (Xu et al 2019) and H + diffusion may be useful for deciphering the timescales of this process.…”
Section: Melt-rock Interactionsmentioning
confidence: 99%
“…interesting evolutions from core to rim of hydrogen defects in orthopyroxene from a garnet lherzolite have also been presented by Xu et al (2019). It shows that the intensity ratio of the 3546 cm -1 band to 3520 cm -1 band increases from core to rim.…”
Section: Introductionmentioning
confidence: 76%
“…The 3546 cm -1 band is not always observed for natural orthopyroxenes. Several studies have reported this band in mantle orthopyroxenes and its height variation from core to rim (Grant et al 2007;Tollan and Hermann 2019;Xu et al 2019). In contrast to the 3546 cm -1 band, the 3460 cm -1 band is scarcely observed in natural mantle orthopyroxenes.…”
Section: Implications Implications For Fingerprinting Hydrogen Of Difmentioning
confidence: 96%
See 2 more Smart Citations